waqf instruments and their role in investing cach waqf - Daho, Mohamed; Fekiki, Souad; Seddiki, Ahmed (Milev Journal of Research and Studies, 2023)
Many Islamic countries have adopted contemporary applications for the organization and management of waqf funds. These applications are realized in the establishment of foundations and funds for Waqf in various organizational forms, and take care of their applications to allow economic and social development. Waqf instruments are among the formulas that have achieved great success in the development and investment of Waqf funds in a number of Islamic countries, with the advantages that have contributed to enriching Islamic finance.